Mountains of water the terraces and traditions of the Ifugao - Corre, Fruto; Rodrigo, Nancy Pe; Santos, Benilda (Bookmark Video, 1998)
This documentary shows how the Ifugaos created and maintained the Ifugao Rice Terraces, the greatest agricultural achievement in human history. It also presents the Ifugao culture: the rituals of the mumbaki, the Hudhud chanted at harvest, the intricate art of weaving and woodcarving.